High‐Latitude Electrodynamics Specified in SAMI3 Using AMPERE Field‐Aligned Currents - A. T. Chartier; J. D. Huba; D. P. Sitaram; V. G. Merkin; B. J. Anderson; S. K. Vines (Space Weather)
Abstract A new technique has been developed to determine the high‐latitude electric potential from observed field‐aligned currents (FACs) and modeled ionospheric conductances. FACs are observed by the Active Magnetosphere and Planetary Electrodynamics Response Experiment (AMPERE), while the conductances are modeled by Sami3 is Also a Model of the Ionosphere (SAMI3). This is a development of the Magnetosphere‐Ionosphere Coupling approach first demonstrated by Merkin and Lyon (2010), https://doi.org/10.1029/2010ja015461. An advantage of using SAMI3 is that the model can be used to predict total electron content (TEC), based on the AMPERE‐derived potential solutions. 23 May 2014 is chosen as a case study to assess the new technique for a moderately disturbed case (min Dst: −36 nT, max AE: 909 nT) with good GPS data coverage. The new AMPERE/SAMI3 solutions are compared against independent GPS‐based TEC observations from the Multi‐Instrument Data Analysis Software (MIDAS) by Mitchell and Spencer (2003), and against Defense Meteorological Satellite Program (DMSP) ion drift data. The comparison shows excellent agreement between the location of the tongue of ionization in the MIDAS GPS data and the AMPERE/SAMI3 potential pattern, and good overall agreement with DMSP drifts. SAMI3 predictions of high‐latitude TEC are much improved when using the AMPERE‐derived potential as compared to Weimer's (2005), https://doi.org/10.1029/2005ja011270 model. The two potential models have substantial differences, with Weimer producing an average 77 kV cross‐cap potential versus 60 kV for the AMPERE‐derived potential. The results indicate that the 66‐satellite Iridium constellation provides sufficient resolution of FACs to estimate large‐scale ionospheric convection as it impacts TEC.